2019
DOI: 10.3390/nu11122909
|View full text |Cite
|
Sign up to set email alerts
|

Allicin Improves Metabolism in High-Fat Diet-Induced Obese Mice by Modulating the Gut Microbiota

Abstract: Allicin, naturally present in the bulbs of the lily family, has anticancer, blood pressure lowering, blood fat lowering and diabetes improving effects. Recent studies have shown that allicin promotes the browning of white adipocytes and reduces the weight gain of mice induced by high-fat diet. While the gut microbiota has a strong relationship with obesity and energy metabolism, the effect of allicin on weight loss via gut microorganisms is still unclear. In this study, we treated obese mice induced by high-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 44 publications
1
43
0
1
Order By: Relevance
“…Moreover, allicin treatment also improved insulin concentrations, suggesting that this compound might have beneficial effects on the remnant pancreatic beta cells. Other beneficial effects of allicin include the improvement in blood glucose, fructosamine, glycated hemoglobin, triglycerides, total cholesterol, high/low-density lipoprotein levels, and reduction in body weight gain and fat deposition [ 63 , 64 ]. On the other hand, it has been proposed that the imbalance in the intestinal microbiota may play a key role in the absorption of nutrients and therefore in the development of metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, allicin treatment also improved insulin concentrations, suggesting that this compound might have beneficial effects on the remnant pancreatic beta cells. Other beneficial effects of allicin include the improvement in blood glucose, fructosamine, glycated hemoglobin, triglycerides, total cholesterol, high/low-density lipoprotein levels, and reduction in body weight gain and fat deposition [ 63 , 64 ]. On the other hand, it has been proposed that the imbalance in the intestinal microbiota may play a key role in the absorption of nutrients and therefore in the development of metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been proposed that the imbalance in the intestinal microbiota may play a key role in the absorption of nutrients and therefore in the development of metabolic diseases. In this regard, it was shown that the effects of allicin on obesity-associated dyslipidemia are related to the modification of the intestinal microbiota [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the report by Kim et al, cloves of A. sativum can decrease the cell size of white adipose tissue in order to suppress the body weight gain [47]. Allicin which is a main compound of A. sativum has improved the metabolism in high-fat diet-induced obese mice by regulating the composition of the intestinal microbiota [48]. Antiobesity and lipid lowering effects of leaves of M. koenigii and its isolated compound, mahanimbine, have been reported with significant reduction of body weight gain [49].…”
Section: Discussionmentioning
confidence: 99%
“…42 Akkermansia muciniphila is another example of gut microbiota species with potential metabolic benefits in preclinical studies, 49 including weight control and increased thermogenesis. 50 The abundance of A. muciniphila in the gut is decreased in obesity and T2D. 20,49 In the proof-ofconcept RCT (not included in any meta-analyses), daily oral supplementation with 10 10 CFU/day of either alive or pasteurized A. muciniphila to overweight or obese participants for 3 months was safe and improved cardiometabolic and inflammatory markers.…”
Section: Dovepressmentioning
confidence: 99%
“…Obesity is associated with gut microbial dysbiosis, which could alter the host's energy absorption and influence intestinal permeability, inflammation, immunity, and multiple other physiologic processes. 14,15,19,20,23,49 Some examples of probiotic-related mechanisms include fermentation of non-digestible nutrients with or without increased energy utilization, 14,15 reduced food intake, 55 increased thermogenesis and energy dissipation, 18,50 and involvement of physiologically active molecules such as gut hormones (eg, GLP-1, peptide YY, endocannabinoids, FGF21). 20,56 Other mechanisms include short-chain fatty acids (SCFA), 20,57 bile acids, neurotransmitters (serotonin, dopamine, gamma-aminobutyric acid), fasting-induced adipose factor, nervous system (enteric, vagus, and brain), and various receptors and their pathways (eg, G-protein coupled receptor 41).…”
Section: Dovepressmentioning
confidence: 99%